2011
DOI: 10.1093/glycob/cwr051
|View full text |Cite
|
Sign up to set email alerts
|

C. albicans increases cell wall mannoprotein, but not mannan, in response to blood, serum and cultivation at physiological temperature

Abstract: The cell wall of Candida albicans is central to the yeasts ability to withstand osmotic challenge, to adhere to host cells, to interact with the innate immune system and ultimately to the virulence of the organism. Little is known about the effect of culture conditions on the cell wall structure and composition of C. albicans. We examined the effect of different media and culture temperatures on the molecular weight (Mw), polymer distribution and composition of cell wall mannan and mannoprotein complex. Strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Cell wall has been considered a dynamic rather than a static assemblage of macromolecules and recent studies have indicated that the Candida cells exhibit altered mannoprotein composition in response to environmental stimuli [39]. Our genome-wide differential gene expression studies of the mutant showed that a large number of hypha-specific genes were upregulated while yeast form-specific Ywp1 protein was clearly downregulated which is commensurate with the morphology of the cells and increased tendency of the mutant cells to show hyper-filamentation.…”
Section: Discussionsupporting
confidence: 63%
“…Cell wall has been considered a dynamic rather than a static assemblage of macromolecules and recent studies have indicated that the Candida cells exhibit altered mannoprotein composition in response to environmental stimuli [39]. Our genome-wide differential gene expression studies of the mutant showed that a large number of hypha-specific genes were upregulated while yeast form-specific Ywp1 protein was clearly downregulated which is commensurate with the morphology of the cells and increased tendency of the mutant cells to show hyper-filamentation.…”
Section: Discussionsupporting
confidence: 63%
“…Similar protein or biomass standardization approaches would be required for testing fungicidal agents against Aspergillus. Culture medium composition (i.e., nutrient-rich versus -poor medium) can also profoundly influence the dynamic and adaptable composition of Candida and Aspergillus cell walls (28,29), which also alters macrophage responses. Consequently, test medium needs to be carefully controlled and individualized to the pathogens of interest and the study objective.…”
Section: Discussionmentioning
confidence: 99%
“…Using single-molecule atomic force probe microscopy Beaussart et al (42) have recently reported that mannans are more abundant on C. albicans hyphae versus yeast. As part of this investigation we attempted to isolate mannan from C. albicans hyphae using mannan specific extractions methods previously reported by our group (43)(44)(45). We were not able to isolate hyphal mannans, except in trace quantities that were too small to be analyzed.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%